Influence of adding different levels of local dried Tarragon (Artemisia dracunculus) as a feed additive on production performance of broiler chicks. - Rashid, Saman Abdulmajid (Sulaimani Journal for Pure and Applied Sciences, 2020)
A total of 240 (one-day-old) unsexed broiler chicks (Ross 308) were used. The experiment included four treatment groups, with four replications per treatment with 15 birds each. The experiment persisted 42 days, the chickens were provided with feed and water ad libitum. Experimental treatments were given basal diet only (T0), basal diet with adding 200 g dried local tarragon (T1), basal diet with adding 400 g dried local tarragon (T2) and basal diet with adding 600 g dried local tarragon (T3). The tarragon additive positively affects the values of daily feed intake,in overall period(1-42 day of age),333.88g/bird/day was the best feed intake which was belonged to T3 treatment. Also,the tarragon additive affects positively protein and energy intake. No significant effects were obtained in body weight gain between the different treatments and within several age periods. Significanteffects were recorded for the resultsof feed conversion ratio and both protein and energy conversion ratio in the age period (29-42 day) and in overall period (1-42 day) but did not affect body weight gain during the trial periods.
Keywords: broiler; tarragon; performance